A guided wave inspection technique for wedge features - Corcoran,J; Leinov,E; Jeketo,A; Lowe,MJS (IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control, 2020)
Numerous engineering components feature prismatic wedge-like structures that require Non-destructive Evaluation (NDE) in order to ensure functionality or safety. This paper focuses on the inspection of the wedge-like seal fins of a jet engine drum, though the capabilities presented will be generic. It is proposed that anti-symmetric flexural edge modes, feature guided waves localised to the wedge tips, may be used for defect detection. Although analytical solutions exist that characterise the ultrasonic behaviour of ideal wedges, in practise real wedges will be irregular (containing for example truncated tips, are built onto an associated structure or have non straight edges) and therefore generic methodologies are required to characterise wave behaviour in non-ideal wedges. This paper uses a semi-analytical finite element (SAFE) methodology to characterise guided waves in wedge-like features with irregular cross-sections to assess their suitability for NDE inspection and compare them to edge modes in ideal wedges. The science and methodologies required in this paper are necessary to select an appropriate operating frequency for the particular application at hand. Additionally, this paper addresses the practical challenge of excitation and detection of flexural edge modes by presenting a piezoelectric based dry-coupled transducer system suitable for pulse-echo operation. The paper therefore presents the scientific basis required for industrial exploitation, together with the practical tools that facilitate use. The study concludes with the experimental demonstration of the edge wave based inspection of a seal fin, achieving a signal-to-noise ratio of 28 dB from a 0.75 mm radial tip defect.